Effects of Mercury Concentration on the Health and Safety of Oil and Gas Workers - Suvarnaraju Palathoti; Manar Al-Rawahi; Riyad Mahfud; Victor Otitolaiye (Occupational Health and Safety Society of Nepal, 2022)
Introduction: The processing of crude oil is characterized by numerous hazards, which have significant health, safety, and environmental impacts on neighboring communities. The occurrence of mercury and its toxic derivatives is considered one of the many negative impacts of oil and gas operations. However, there is limited research on mercury and its negative effects on workers in the Gulf Cooperation Council (GCC) region. This study examines the occurrence, exposure, and symptoms of mercury on the health and safety of oil and gas workers in Oman. It also explores the acute/chronic effects of mercury poisoning on the maintenance and inspection workers, who are more prone to the adverse effects of mercury poisoning during oil and gas operations. Methods: The two-pronged approach of literature review and survey questionnaire was used to deduce the effects of mercury exposure and poisoning using 68 respondents with 1 - 6 years of working experience in the sector. Results: Based on the questionnaire response rate of 72%, the results showed that over 90% of participants had experienced symptoms of elemental, organic, and methyl mercury poisoning. The common symptoms experienced are headaches, insomnia, weakness, hearing impairment, visual and sensory abilities. However, the respondents who experienced methyl mercury (MeHg) symptoms are due to consuming seafood and cigarettes, whereas elemental and organic mercury symptoms are due to oil and gas operations. Conclusion: The findings highlight the need for robust health and safety measures to effectively detect, monitor and eliminate mercury compounds responsible for poisoning maintenance and inspection workers.